The Notion of “Moral Firm” and Distributive Justice in an Islamic Framework - Azid, Toseef; Rawashdeh, Osamah H (Intellectual Discourse, 2018)
This paper discusses conventional and Islamic concepts of distributive justice, and develops propositions for the establishment of firms deemed to be moral firms from Islamic perspective. Generally, distributive justice implies that goods should be distributed among members of the community according to their standing in society. In the Islamic scenario, however, the positive and the normative aspects work simultaneously. The management of a firm seeks not only to earn profit in this world but also to get reward in the life-hereafter. Thus, it is duty of a firm to serve the community and look after its shareholders, employees and consumers. This paper also postulates that in a cooperativecum- competitive environment, firms have the same responsibilities as other members of the society. Hence, it is the duty of the firm to maintain distributive justice among its stakeholders. It is also suggested that in the framework of the Shariʽah, if there are any imperfections in the market, it is the responsibility of the state to remove them. This paper also discusses the social and moral responsibilities of the firms which claim that their products are Shariʽahcompliant.